ESTIMASI SUMBER DAYA BAUKSIT MENGGUNAKAN METODE ORDINARY KRIGING DI KECAMATAN MELIAU, KALIMANTAN BARAT: ESTIMATION OF BAUXITE RESOURCES BASED ON ORDINARY KRIGING METHODS AT KECAMATAN MELIAU, WEST KALIMANTAN - Westia Alifah Surya Pratiwi; Denny Lumban Raja; Priatna; Sarah Mutia; Dedi Sunjaya (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2024)
The estimation of mineral resources is crucial in mining, particularly in determining production targets, pit design, and investment decisions. Accurate resource estimation results will facilitate optimal mine planning. The objective of this study is the application of estimation techniques that consider geostatistics, namely ordinary kriging, in estimating bauxite deposit resources. The research location is in the laterite arc of West Kalimantan. The data used for estimation are exploration data from 212 test pit locations. The aim of this study is to identify the lithology of the bauxite deposit, distribution of grades, and estimate bauxite resources as well as determine the optimal spacing of test pits as a basis for resource classification in the study area. Petrographic analysis was conducted on four samples to determine the lithology. The study results indicate that the lithology forming the bauxite deposit consists of granodiorite, quartz diorite, and granite. The bauxite deposits in the study area are predominantly derived from granodiorite with high content, thus characterizing the bauxite as kaolinitic bauxite. The bauxite resource estimation results, based on a cut-off grade of >35%, <8%, dan ≤30%, amounted to 722,720 tons of washed bauxite, with an average grade of 39,78% , dan 25,05% , with a concretion factor of 48.44%. The inferred washed bauxite resources are 146,962 tons, the indicated resources are 550,482 tons, and the measured resources are 221,643 tons. Based on the sill variogram calculation, the optimal spacing for test pits for bauxite exploration in the study area with resource classification is 100 m for inferred, 50 m for indicated, and 25 m for measured resources.